Prostaglandin metabolite induces inhibition of TRPA1 and channel-dependent nociception - Weng Yingqi; Batista-Schepman Patricia A; Barabas Marie E; Harris Eli Q; Dinsmore Thomas B; Kossyreva Elena A; Foshage Audra M; Wang Michelle H; Schwab Matthew J; Wang Victoria M; Stucky Cheryl L; Story Gina M (SAGE Publishing, 2012)
Abstract Background The Transient Receptor Potential (TRP) ion channel TRPA1 is a key player in pain pathways. Irritant chemicals activate ion channel TRPA1 via covalent modification of N-terminal cysteines. We and others have shown that 15-Deoxy-Δ12, 14-prostaglandin J2 (15d-PGJ2) similarly activates TRPA1 and causes channel-dependent nociception. Paradoxically, 15d-PGJ2 can also be anti-nociceptive in several pain models. Here we hypothesized that activation and subsequent desensitization of TRPA1 in dorsal root ganglion (DRG) neurons underlies the anti-nociceptive property of 15d-PGJ2. To investigate this, we utilized a battery of behavioral assays and intracellular Ca2+ imaging in DRG neurons to test if pre-treatment with 15d-PGJ2 inhibited TRPA1 to subsequent stimulation. Results Intraplantar pre-injection of 15d-PGJ2, in contrast to mustard oil (AITC), attenuated acute nocifensive responses to subsequent injections of 15d-PGJ2 and AITC, but not capsaicin (CAP). Intraplantar 15d-PGJ2-administered after the induction of inflammation-reduced mechanical hypersensitivity in the Complete Freund's Adjuvant (CFA) model for up to 2 h post-injection. The 15d-PGJ2-mediated reduction in mechanical hypersensitivity is dependent on TRPA1, as this effect was absent in TRPA1 knockout mice. Ca2+ imaging studies of DRG neurons demonstrated that 15d-PGJ2 pre-exposure reduced the magnitude and number of neuronal responses to AITC, but not CAP. AITC responses were not reduced when neurons were pre-exposed to 15d-PGJ2 combined with HC-030031 (TRPA1 antagonist), demonstrating that inhibitory effects of 15d-PGJ2 depend on TRPA1 activation. Single daily doses of 15d-PGJ2, administered during the course of 4 days in the CFA model, effectively reversed mechanical hypersensitivity without apparent tolerance or toxicity. Conclusions Taken together, our data support the hypothesis that 15d-PGJ2 induces activation followed by persistent inhibition of TRPA1 channels in DRG sensory neurons in vitro and in vivo. Moreover, we demonstrate novel evidence that 15d-PGJ2 is analgesic in mouse models of pain via a TRPA1-dependent mechanism. Collectively, our studies support that TRPA1 agonists may be useful as pain therapeutics.